Agricultural-food systems and environmental health in the era of Covid-19 - Hamidi, Nur Hidayah; Ahmed, Osumanu Haruna; Musah, Adiza Alhassan; Marsal, Cristalina Jalil; Shahlehi, Syahirah; Basir, Khairul Hidayatullah; Mohd Nasir, Mohd Hamzah (Springer, 2025)
The emergence of novel coronavirus in Wuhan city of China has become a global health emergency. This health pandemic has been affecting normal daily life in every sector around the world particularly the agriculture-food ecosystem. Therefore, this review presents information on the effects of the ongoing global pandemic on the agricultural-food ecosystems and the probable environmental resilience and impact during COVID-19 pandemic years. The COVID-19 pandemic being the most recent in the line of coronavirus zoonotic infections, has created a severe disruption never before in the human history because it affects all work of life including exploiting social, economic, institutional, and environment vulnerabilities and intensify food insecurity, yet pollution is declining and nature is recovering its natural state. Preven-tive measures implemented by many countries are likely to affect vulnerable groups including workers, small scale farmers, low-income families, and students faced the worst hit among all. Waste generation is in the course of the pandemic is alarming, if not worrying. Educational institutions are searching ways to fill the loss of learning. The COVID-19 pandemic has given us the opportunity to introduce online learning. The COVID-19 pandemic calls for urgent policy solutions to keep the economy afloat and people to keep their jobs and incomes. Although the pandemic creates some major issues for the food system, it also presents a good chance to speed up transformation in the food and agriculture industry that will improve its resilience to a variety of threats including climate change.